The History of Cooperativism in Colombia: Milestones and Periods - Pardo Martínez, Luz Patricia; Huertas de Mora, María Victoria (Cooperativismo & Desarrollo, 2014)
The line of research that supports this article aims to clarify the following fundamental axes: first of all, to identify which types of cooperatives have arisen in Colombia, along with their characterization, and secondly to establish the milestones that have marked and defined historic periods. The research focuses on addressing the feasibility, usefulness and correspondence of cooperative organizations with the philosophical doctrine of the sector; analyzing the contribution of cooperatives, according to their practices, to development and to boosting their social dimension, along with the influence of their behaviors on consolidation of such organizations with respect to local and national communities; and finally, to establish historical periods of development of cooperative organizations in Colombia.